What Makes a Good Piece of Poetry: an Attempt at Subjective Analysis - Kulchytska, O.; Bodnarchuk, M. (Journal of Vasyl Stefanyk Precarpathian National University, 2016)
One of the factors in the popularity of Michael Swan’s poetry is a unique combination of a comparatively simple form and deep, subtle meanings that even an inexperienced reader cannot but sense. In linguistics, the phenomenon is dubbed implicitness. In Michael Swan’s poetic texts, implicit meanings are generated through the violation of the maxims of the co-operative principle (conversational implicature) and/or through the use of specific techniques: simplicity of outward form, tropes, irony, attention to detail, contrast and opposition, repetition, punch line, the effect of the author’s presence in the text or distancing from the content